2010
DOI: 10.1021/ac101581n
|View full text |Cite
|
Sign up to set email alerts
|

Hyphenated Technique for Releasing and MALDI MS Analysis of O-Glycans in Mucin-Type Glycoprotein Samples

Abstract: We developed an automatic apparatus for the release of O-glycans from mucin-type glycoproteins and proteoglycans (Matsuno, Y.-k.; Yamada, K.; Tanabe, A.; Kinoshita, M.; Maruyama, S.-z.; Osaka, Y.-s.; Masuko, T.; Kakehi, K. Anal. Biochem. 2007, 363, 245-257. Yamada, K.; Hyodo, S.; Matsuno, Y. K.; Kinoshita, M.; Maruyama, S. Z.; Osaka, Y. S.; Casal, E.; Lee, Y. C.; Kakehi, K. Anal. Biochem. 2007, 371, 52-61). The method allows rapid release of O-glycans as the reducing form within 10 min. In the present study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…Our lectin selection can be further justified by the composition of the human serum O-glycan pool. The dominance of the monosialylated mucin core-1 O-glycan, NeuAcα2–3Galβ1–3GalNAcα in human serum O-glycoproteins has been demonstrated by two independent studies [36, 37]. This structure represents more than 60% of the glycans, followed by the diasialo and asialo variants, at approximately 20% and 10%, respectively [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our lectin selection can be further justified by the composition of the human serum O-glycan pool. The dominance of the monosialylated mucin core-1 O-glycan, NeuAcα2–3Galβ1–3GalNAcα in human serum O-glycoproteins has been demonstrated by two independent studies [36, 37]. This structure represents more than 60% of the glycans, followed by the diasialo and asialo variants, at approximately 20% and 10%, respectively [37].…”
Section: Discussionmentioning
confidence: 99%
“…We aimed at the isolation of glycopeptides modified with mucin-type core-1 structures, as this glycoform has been reported to be the most abundant in human serum [36]: NeuAcα2–3Galβ1–3GalNAcα (~60%), NeuAcα2–3Galβ1–3(NeuAcβ2–6)GalNAcα (~20%), and Galβ1–3GalNAcα (~10%) represent ~90% of the total O-glycan pool [37]. Considering the wide dynamic range of serum protein levels, and the expected heterogeneity of O-glycosylation, we followed multistep enrichment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…More than column selection, sample preparation is a big issue for O ‐glycan analysis. For non‐reducing β‐elimination, LiOH , NH 3 , and H 2 NNH 2 were used. Comparisons between H 2 NNH 2 , NH 3 , and NaOH , or NaOH, NH 3 , and Me 2 NH were carried out.…”
Section: Analysis Of N‐ and O‐glycansmentioning
confidence: 99%
“…Over the years, a number of different reagents for nonreductive release have been developed. Chai et al (1997) reported the use of 70 % (w/v) aqueous ethylamine and Yamada et al (2010) reported the use of lithium hydroxide in an automatic setup, but the overall reaction Possible isomeric structures are given in different colors, and key product ions derived thereof are denoted in the respective color. Nonspecifi c product ions are labeled in black.…”
Section: Nonreductive β -Eliminationmentioning
confidence: 99%